2D speckle-tracking in assessment of myocardial strain in children with hypertrophic cardiomyopathy: 2D sledenje ultrazvočnega vzorca deformacije miokarda pri otrocih s hipertrofično kardiomiopatijo - Chernykh, Nadezhda; Tarasova, Alla; Groznova, Olga (Acta Medico-Biotechnica, 2022)
Purpose: To assess the myocardial strain in children with hypertrophic cardiomyopathy (HCM).Methods: A total of 61 patients aged between 7 and 17 years with an asymmetric form of HCM underwent an ultrasound examination of the heart using standard techniques. An assessment of the left ventricular systolic function was performed using the two-dimensional (2D) speckle-tracking mode with analysis parameters that included global and segmental longitudinal, circumferential, and radial myocardial strains. Strain data for the subendocardial and subepicardial layers for each segment of the left ventricle, as well as their total values, were determined.Results: Global longitudinal strain and longitudinal strain rate were dec reased due to the impaired contractility of hypertrophied myocardial segments in 100% of cases of non-obstructive and obstructive HCM forms. A decrease in global, radial, and circumferential strain parameters and their rates has been observed in all children with an obstructive form of HCM and 39 (86.6%) patients with non-obstructive form. At the same time, there was a statistically significant difference between strains and strain rates in children with a non-obstructive form of HCM in comparison to those with an obstructive form of the disease.Conclusion: Changes in myocardial strains observed using the 2D speckle-tracking mode in children with HCM indicate early systolic dysfunction of the left ventricle. Longitudinal strain was the most sensitive compared to radial and circumferential types. It was statistically significantly different in children with an obstructive form of HCM compared to those with non-obstructive form of the disease. These results are important for early therapy initiation and, therefore, may improve prognosis in children with HCM.
Keywords: 2D speckle tracking, strain, echocardiography, hypertrophic cardiomyopathy, early diagnosis, treatment, children